Development of Community and Digital Marketing Based Bongo Religious Tourism Village - Jafar Lantowa; Nikmasari Pakaya; Desrika Talib (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Bongo religious tourism destinations consist of homestays, Dulanga beach, Bongo Tourist Park, Walima Emas mosque, and the Central Museum of Indonesian Wood Fossils. This tourist destination also provides a variety of souvenirs and culinary specialties of Bongo, which SMEs of Bongo Village market. These various tourism potentials are unfortunately still not widely known by tourists. The team's initial discussion with the management of the Bongo Village Tourism Awareness Group (POKDAWRIS) showed that there is a potential for tourism villages that need to be developed but is still constrained by the lack of community involvement and the knowledge and skills of human resources in marketing digital-based tourist destinations. Therefore, the solutions that we apply to deal with these problems are 1) increasing community participation, 2) making by rearranging the infrastructure of the Bongo Religious Tourism Village with the concept of a Halal Tourism Village, 3) implementing a strategy for developing local tourism wisdom in Bongo Village based on CBT and Digital Marketing, 4) increasing tourist attraction through Digital Marketing, 5) creating and managing digital marketing media, and 6) implementing program sustainability strategies. The implementation of the activities carried out included 1) dissemination of the development of the Bongo religious tourism village, 2) workshops on the development of potential religious tourism villages based on Community and Digital Marketing, 3) English training for Bongo Village tour guides, 4) the creation of website pages and applications for marketing Bongo religious tourism village, 5) training on the use of applications and websites for Tourism Awareness Groups, and 6) training on institutional and organizational management of POKDARWIS.